The "Triple-A" Strategy for Enhancing Supply Chain Performance - Suarsa, Senny Handayani; Nurul Pangestika; Asaretkha Adjane Annisawati (Journal of Marketing Innovation (JMI), 2024)
This study addresses challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in the Cibaduyut shoe center, Bandung, Indonesia, focusing on their management issues, particularly the timely acquisition of crucial raw materials. The research centers on evaluating the effectiveness of the Triple A strategy (Agility, Adaptability, and Alignment) in improving supply chain performance (SCP) within these MSMEs. The study aimed to understand how this strategy, addressing prevalent challenges such as delays in raw material acquisition, can enhance overall business performance. Data collection involved a convenience sampling technique, distributing questionnaires to 76 business units. The questionnaire aimed to gather insights into the Triple A strategy's implementation and its perceived impact on SCP. Collected data underwent thorough validation for reliability, and multiple linear regression analysis was employed to test relationships between Triple-A components and SCP. The research highlights the Triple A strategy's pivotal role in revitalizing business units by minimizing production costs and reducing raw material waste through effective collaboration with suppliers, reinforcing its potential as a strategic tool for optimizing supply chain performance in MSMEs.